Does competition between Pardosa pseudoannulata and Menochilus sexmaculatus reduce the predation rate on brown planthopper? - Septriani, Utari; Syahrawati, My; Arneti, Arneti (CROPSAVER, 2023)
Pardosa pseudoannulata and Menochilus sexmaculatus are classified as natural enemies of the brown planthopper or BPH (Nilaparvata lugens). This study aimed to determine the effect of differences in density on mortality and their predation rate in suppressing the BPH population. This study used a completely randomized design of 15 treatments and 3 replications. The treatments consisted of different densities of two predators (1, 2, and 3 individuals). The variables observed were predator mortality, predation rate, competition between predators, and competition behavior. The results showed that competition between predators at different densities was not directly related to predator mortality and the predation rate of joint predators. Predator density tended to increase the predation rate, especially on M. sexmaculatus (R=0.894), while the density of P. pseudoannulata and joint predators was moderate (Rpardosa=0.587, Rjoint=0.522). M. sexmaculatus won the competition when its population increased. Equal competition occurred in the composition of 1 P. pseudoannulata and 3 M. sexmaculatus (P1M3); in this composition, no deaths were found due to competition, with the predation rate reaching 86.7%. Cannibalism dominates intraspecific competition between individuals of P. pseudoannulata, while interspecific competition occurs between the two species, causing sub-lethal effects.